Managing full-scale dry anaerobic digestion: semi-continuous and batch operation - Rocamora, Ildefonso; Wagland, Stuart T.; Rivas Casado, Monica; Hassard, Francis; Villa, Raffaella; Peces, Miriam; Simpson, Edmon W.; Fernández, Oliver; Bajón Fernández, Yadira (Elsevier, 2022)
Dry anaerobic digestion usually results in inhibitors accumulation, which can be solved by adapting operation. Multiple strategies targeting increased stability are implemented in full-scale, but impacts are poorly documented. Two full-scale dry AD plants treating organic fraction of municipal solid waste (OFMSW) were investigated: a semi-continuous plant with compost addition and a batch plant testing different percolate recirculation strategies and inoculum to substrate ratios. Regression tree analysis was used to evaluate the effect of these strategies on methane yields and inhibitors accumulation. Compost addition in the semi-continuous plant reduced volatile fatty acids content but dropped methane flow up to 10 % when compost constituted over 10.1 % in weight of the incoming feedstock. This reduction was linked to the limited availability of easily degradable material in the compost. In batch dry AD, methane yields increased as percolate recirculated raised up to a range of 182–197 m3 (0.342–0.363 m3/t of biomass mix). Recirculation of higher percolate volumes reduced methane production, probably linked to pile compaction and inhibitors accumulation. The ratio of OFMSW, digestate and woodchip (bulking agent) fed was determinant, and methane production was higher when digestate was over 43.1 %, waste between 45 % and 47.5 % and woodchip over 8.2 % in weight in as received basis. Woodchip influenced percolation through the pile and supported reduced total ammonia levels of 3.2 g/l when kept over 8.2 %, which raised to 5.2 g/l for lower values.
Keywords: Regression tree; Operational parameters; Percolate recirculation; Bulking agent; Compost addition; Hydrogenotrophic archaea